Diversity of the non-targeted metabolomic data across various varieties of Cloves (Syzygium spp.)Figshare - Jakty Kusuma; Analianasari; Anung Wahyudi; Muhammad Khalid Abdullah; Ahmad Zainul Hasan; Imam Asrowardi; Fitriani; Muhammad Tahir (Data in Brief)
Cloves (Syzygium aromaticum), a tree in the Myrtaceae family, are indigenous to the Maluku Islands in Indonesia and are widely utilized as a spice. Essential oils are commonly extracted from clove leaves, flower buds, and stalks. However, due to supply constraints, other clove species, notably Syzygium obtusifolium, are sometimes used as substitutes, leading to lower-grade essential oils. Here, we employed a non-targeted mass-spectrometry-based metabolomics approach to characterize the metabolic profiles of leaves from ten clove varieties, including S. obtusifolium. We identified and quantified 427 metabolites across various metabolic pathways. The metabolomics data for all samples are publicly available at the Figshare repository under 10.6084/m9.figshare.27212016. The data can be accessed directly at https://figshare.com/s/f4a40b7903b6a946b203.